2017
DOI: 10.7150/jca.21444
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of CD163+ and CD68+ Tumor-associated Macrophages in High-risk HPV-related Cervical Cancer

Abstract: Objective. To explore the influence of M2-polarized tumor-associated macrophages (TAMs) on high-risk human papillomavirus (hr-HPV)-related cervical carcinogenesis and metastasis.Methods. CD68+ and CD163+ macrophages were examined immunohistochemically in a series of 130 samples, including 26 cases of normal cervical tissues, 59 cases of cervical intraepithelial neoplasia (CIN), and 45 cases of squamous cell carcinoma (SCC), and the results were statistically analyzed. The macrophage count was corrected for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 33 publications
4
79
0
1
Order By: Relevance
“…Immunohistochemistry (IHC) was performed as previously described . Briefly, consecutive 4‐µm paraffin sections were deparaffinized and rehydrated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry (IHC) was performed as previously described . Briefly, consecutive 4‐µm paraffin sections were deparaffinized and rehydrated.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry (IHC) was performed as previously described. 26 Briefly, consecutive 4-µm paraffin sections were deparaffinized and rehydrated. Endogenous peroxidase activity was blocked by incubation for 30 min with 3% H 2 O 2 in methanol at room temperature (RT).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…These effects result in promotion of carcinogenesis and metastasis. Although not specific to HPV‐associated OPSCC, TAMs are linked to poor prognosis, progression of disease, locoregional metastasis, and higher grade lesions . The M1 phenotype, however, is associated with tumor regression and inducing HPV clearance by favoring a TH1 response .…”
Section: Role Of Innate Immunity In Hpv + Opsccmentioning
confidence: 99%
“…It was reported that poor prognosis is linked to increased levels of CD163 (TAM marker with M2 phenotype), CSF-1 (colony-stimulating factor-1), major regulator of macrophage lineage, and Arginase-1 (Arg-1) – markers of TAM’s activity – in several cancers including the HPV-related ones [ 12 , 25 , 28 ]. Increased infiltration of CD163 macrophages in stromal and peri-tumoral areas were associated with malignancy progression, lymph node metastasis, higher FIGO stages [ 29 ], higher lesion grades and cervical cancer specimens [ 28 , 30 ].…”
Section: Macrophages and Mast Cellsmentioning
confidence: 99%